2000
DOI: 10.1007/s007020070090
|View full text |Cite
|
Sign up to set email alerts
|

An association study between two missense variations of the benzodiazepine receptor (peripheral) gene and schizophrenia in a Japanese sample

Abstract: The benzodiazepine receptor (peripheral) (BZRP) mainly localized on glial cells plays a role in neurosteroid synthesis, and increases with glial proliferation. We have recently reported a significant decrease in the density of BZRP labeled by [3H] PK 11195 in the postmortem brain of chronic schizophrenics, suggesting that dysfunctions of the BZRP are involved in the pathophysiology of schizophrenia. We screened 11 patients with schizophrenia and 10 controls, which were used in a previous postmortem study, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…This strongly supports the assumption that progesterone-derived neuroactive steroids contribute to the actions of olanzapine but not of risperidone and haloperidol (Barbaccia et al, 2001;Marx et al, 2000Marx et al, , 2003. The recent reports support our observation that levels of GABAergic neuroactive steroid are significantly lower in schizophrenics (Kurumaji et al, 1997(Kurumaji et al, , 2000. Moreover, numerous evidences suggest that variations in the steady-state level of neuroactive steroids, especially ALLO in brain, may be relevant to pathophysiology of a range of psychiatric disorders (Guidotti et al, 2000(Guidotti et al, , 2001.…”
Section: Discussionsupporting
confidence: 90%
“…This strongly supports the assumption that progesterone-derived neuroactive steroids contribute to the actions of olanzapine but not of risperidone and haloperidol (Barbaccia et al, 2001;Marx et al, 2000Marx et al, , 2003. The recent reports support our observation that levels of GABAergic neuroactive steroid are significantly lower in schizophrenics (Kurumaji et al, 1997(Kurumaji et al, , 2000. Moreover, numerous evidences suggest that variations in the steady-state level of neuroactive steroids, especially ALLO in brain, may be relevant to pathophysiology of a range of psychiatric disorders (Guidotti et al, 2000(Guidotti et al, , 2001.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the urine of both subjects was negative for common drugs of abuse. To explore possible causes of the unusual brain uptake, we plan to examine polymorphisms of the PBR gene including those reported (Kurumaji et al, 2000) and also perform in vitro binding to PBRs located on white blood cells.…”
Section: Nonbindersmentioning
confidence: 99%
“…We have reported the two missense polymorphisms of the nucleotide sequence in the exon 4, i.e., Ala147Thr and His162Arg [Kurumaji et al, 2000]. Several studies have reported some evidence for linkage between the mood disorders and a genetic marker located on 22q11-q13 [DeteraWadleigh et al, 1999;Edenberg et al, 1997;Lachman et al, 1997].…”
Section: Introductionmentioning
confidence: 97%